ANALISA DAYA DUKUNG PONDASI TIANG PANCANG PADA PROYEK PEMBANGUNAN GEDUNG KULIAH TERPADU POLITEKNIK PARIWISATA PALEMBANG - Arfan, Muhammad; Setiawati, Mira; Kateni, Darul (Universitas Muhammadiyah Palembang, 2020)
This researcher focused on an exprimental study of the carryng capasity of a group pile foundation used in the palembang tourism polytechnic integrated lecture building, bearing in mind that this type of foundation is capable of supporting a considerable burden. To determine the carryng capacity of the pile foundation carrying capacity calculation based on N-SPT data using tarzaqi and Peck (1948)Researches conducted at point P6 2b at the integrated lecture building in palembang tourism polytechnic using diameter variation of Ø30, Ø35, Ø40, Ø60 with depth variations of 24,25,26 meters and quality of concreate k-500.The result of the carrying capacity of the group pile foundation,at point P6 2b by using the calculation of tarzaqi and peck (1948) amounted to 3803. 19 Kn. From the calculation of variations at point P6 2b the e Øen Ø30 is a depth of 35.5 m with a volume of 15.60 m3 with KnKeywords: Efficiency of bearing carryng, variations in group piles, Terzaghi and peck (1948)